A review on clinical implications of S100 proteins in lung diseases - Raveendran, Vineesh V.; AlQattan, Somaya; AlMutairy, Eid (Frontiers in Medicine, 2025)
The S100 family of proteins plays a pivotal role in the pathogenesis of lung diseases, including asthma, chronic obstructive pulmonary disease (COPD), cystic fibrosis, pulmonary arterial hypertension (PAH), pulmonary fibrosis, lung cancers, acute lung injury, acute respiratory distress syndrome, COVID-19, and lung transplantation. This review comprehensively examines the contributions of S100 proteins to the progression of these disorders, focusing on their potential as diagnostic and prognostic biomarkers, as well as therapeutic targets. S100A protein-mediated key molecular mechanisms that influence inflammation, airway remodeling, fibrosis, and tumorigenesis in the lungs are discussed. The importance of their normal function is evident from the observation that simultaneous mutations in S100A3 and S100A13 predispose individuals to early-onset pulmonary fibrosis, underscoring their critical role in lung health. Furthermore, sustained S100 protein elevation is explored in the context of long COVID, shedding light on its role in chronic inflammation. These proteins act as damage-associated molecular patterns (DAMPs), activating immune pathways via receptors like TLR4 and RAGE, thereby driving inflammation and immune cell recruitment. Notably, in lung transplantation, elevated levels of S100A8, S100A9, and S100A12 serve as early biomarkers of graft rejection and complications such as graft-vs.-host disease, which indicates their role in mediating immune responses and transplant outcomes. While promising, the clinical application of S100 proteins faces challenges, including disease-specific variability and the need for robust validation across diverse populations. This narrative review underscores the dual potential of S100 proteins as biomarkers and therapeutic targets in respiratory medicine while emphasizing the importance of overcoming current limitations through targeted research and clinical trials.